1997
DOI: 10.1074/jbc.272.15.9690
|View full text |Cite
|
Sign up to set email alerts
|

GTP Cyclohydrolase I Feedback Regulatory Protein Is a Pentamer of Identical Subunits

Abstract: GTP cyclohydrolase I feedback regulatory protein (GFRP) mediates feedback inhibition of GTP cyclohydrolase I activity by tetrahydrobiopterin and also mediates the stimulatory effect of phenylalanine on the enzyme activity. To characterize the molecular structure of GFRP, we have purified it from rat liver using an efficient step of affinity chromatography and isolated cDNA clones, based on partial amino acid sequences of peptides derived from purified GFRP. Comparison between the amino acid sequence deduced fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
47
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 23 publications
2
47
0
Order By: Relevance
“…Rat recombinant GTPCHI and GFRP were expressed in Escherichia coli cells, purified, and crystallized as described (13,16,17). The stimulatory complex (5 mg͞ml) was crystallized from 24% (vol/vol) 2-methyl-2,4-pentanediol͞75 mM Tris⅐HCl (pH 7.5)͞50 mM KCl͞5 mM phenylalanine.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rat recombinant GTPCHI and GFRP were expressed in Escherichia coli cells, purified, and crystallized as described (13,16,17). The stimulatory complex (5 mg͞ml) was crystallized from 24% (vol/vol) 2-methyl-2,4-pentanediol͞75 mM Tris⅐HCl (pH 7.5)͞50 mM KCl͞5 mM phenylalanine.…”
Section: Methodsmentioning
confidence: 99%
“…GTPCHI is a decamer of 260 kDa with a subunit consisting of 230 amino acid residues (15), and GFRP is a pentamer of 50 kDa with a subunit consisting of 83 amino acid residues (16). Recently, we showed that both stimulatory and inhibitory GTPCHI⅐GFRP complexes consist of one molecule of decameric GTPCHI and two molecules of pentameric GFRP (13).…”
mentioning
confidence: 99%
“…Interestingly, millimolar level concentrations of L-Phe have been shown to reverse this feedback inhibition without causing dissociation of the GFRP⅐GTPCH complex (37). In the absence of BH4, L-Phe triggers GFRP binding to GTPCH resulting in increased GTPCH activity at low levels of GTP substrate (35,38). Because L-Phe is potentially neurotoxic, the ability of L-Phe to stimulate GTPCH activity may have evolved to provide an abundant supply of BH4 cofactor for optimal activity of phenylalanine hydroxylase.…”
mentioning
confidence: 99%
“…At the post-transcriptional level, BH 4 was shown to inhibit, and phenylalanine to stimulate, GCH activity through interaction with GFRP, a GTP cyclohydrolase I feedback regulatory protein [9]. GCH, which is a homodecameric protein, shows positive cooperativity against the GTP substrate [10] and phenylalanine changes the substrate velocity curve from sigmoidal to hyperbolic [11].Recent biophysical studies suggest a stimulatory effect of Zn 2+ [12] and Ca 2+ [13] on GCH activity. By crystallographic analysis using purified Escherichia coli enzyme [14], an N-terminally truncated form of the recombinant human enzyme [12], and a stimulatory complex of rat GCH and GFRP induced by phenylalanine [15], Zn 2+ was shown to be bound to the active centre of the homodecameric GCH enzyme.…”
mentioning
confidence: 99%
“…At the post-transcriptional level, BH 4 was shown to inhibit, and phenylalanine to stimulate, GCH activity through interaction with GFRP, a GTP cyclohydrolase I feedback regulatory protein [9]. GCH, which is a homodecameric protein, shows positive cooperativity against the GTP substrate [10] and phenylalanine changes the substrate velocity curve from sigmoidal to hyperbolic [11].…”
mentioning
confidence: 99%